Tout un Monde An Interdisciplinary Approach to Intermediate French - Soueid, Alicia (Open textbook library., 2019)
This book is intended for use with intermediate level college French classes. Its multidisciplinary approach introduces students to topics and vocabulary associated with fields such as medicine, advertising, travel, business, agriculture, and relationships.